The Pathological effct of Aeromonas caviae bacteria and clinical chemistry – In rats - Al-Qaese, Bshra Ibrahem (The Iraqi Journal of Veterinary Medicine, 2003)
The study aimed at Investigating the effect of Aeromonas caviae baceria which cause Systemic and Local infection on the gross and histopathological changes in rats, also study the behaviour, blood picture and clinicl chemistry tests ( Total protein ,GOT and GPT enzymes ) in blood. A clinical samples from (120) infected patients were taken from Urin , Stool , wound Smears and cerebrospinal fluid collected From Kendey and Yarmmuk hospitals, In Baghdad area Thirty White male rats divided into three groups : The 1" group injected intraperitoneal with (10)' cell /ML,2nd group injected with PBS and the 3rd group (negative control ). Were used in this examination .. The gross and histopathological Changes in (Lung, liver ,Kidney ,Muscles ,heart ,spleen ,intestine and Nervous System ) of infected rats Shows Whole damage and necrosis with congestion and haemorrhege also different kinds of inflammatory cells Infiltrated in above organs like : neutrophiles, eosinophiles and Macrophages Blood picture showed significant P<0.05 decrease in RBCs count Hb Concentrration and PCV level, and an increase in WBC count, with decrease blood total protein and increase GPT and GOT enzymes in blood.